New Zealand species of the shore-fly genus Nostima Coquillett(Diptera: Ephydridae) - Edmiston, James F.; Mathis, Wayne N. (Zootaxa, 2007)
The shore-fly genus Nostima Coquillett is first reported from New Zealand in a revision of the three species now known to occur there. Species included are: Nostima kiwistriata sp. n., N. negramaculata sp. n. and N. duoseta Cresson. The latter species was first described from Australian specimens and is here reported to occur widely in New Zealand. Detailed locality data from New Zealand are provided for each species. The phylogenetic relationships between the New Zealand species and species from other geographical regions are presented. A key to the species of Nostima occurring in New Zealand is presented.